Fold distribution and multilayer properties, a case study from the Lurestan province of Iran - Casciello, E.; Vergés, J.; Hunt, D. W.; Blanc, E. (TRABAJOS DE GEOLOGÍA, 2009)
The characteristics of folds of the southern Lurestan province have been studied in terms of wavelength and axial-length distribution. The large variability of these parameters occurs in relation to facies changes within the Cretaceous Bangestan group which acts as the competent carbonate unit that governs bucking in this region. Disharmonic folding of the overlying Asmari formation occurs where the thickness of the interposed incompetent units exceeds a critical thickness that leaves the Asmari limestone outside of the zone of contact strain of the Bangestan buckles.